Forward and backward electron yield ratio for α-particle induced emission from different materials - Zhurenko, V.P.; Kononenko, S.I.; Kalantaryan, O.V.; Avotin, S.S.; Rokhmanov, N.Ya. (Вопросы атомной науки и техники, 2021)
In this work, the ratio of forward and backward electron yields for emission induced by the isotropic flux of α-particles from zinc was measured. On the basis of the measured values and experimental data obtained in earlier experiments for other materials, a systematization of the electron yield ratio for forward and backward emission was done, and a relationship of the ratio with stopping power of an ion in a substance was found. The dependence of work function for various materials on the ratio of the electron emission yields was analyzed. Виміряне відношення коефіцієнтів емісії електронів на простріл і на відбиття, яка індукована ізотропним потоком α-частинок з цинку. На основі виміряних значень і експериментальних даних, отриманих у попередніх експериментах для інших матеріалів, проведена систематизація відношення коефіцієнтів на простріл і відбиття, і встановлено зв’язок цього параметра з питомими іонізаційними втратами іона в речовині. Проаналізовано залежність роботи виходу електронів для різних матеріалів від відношення коефіцієнтів емісії. Измерено отношение коэффициентов эмиссии электронов на прострел и на отражение, которая индуцирована изотропным потоком α-частиц из цинка. На основе измеренных значений и экспериментальных данных, полученных в более ранних экспериментах для других материалов, проведена систематизация отношения коэффициентов на прострел и отражение, и установлена связь этого параметра с удельными ионизационными потерями иона в веществе. Проанализирована зависимость работы выхода электронов для различных материалов от отношения коэффициентов эмиссии.